Sustitución del carbonato de calcio inorgánico por carbonato de calcio biogénico obtenido de residuos de las vieiras (argopecten purpuratus) en las industrias peruanas - Del Castillo Luis, Darlyn Eliane (2023)
Peru is the world's third largest producer of scallops or shells, an industry that generates various economic and social benefits, but, at the same time, generates an environmental problem since scallop shells are disposed of in landfills. However, these can be transformed into biogenic pulverized calcium carbonate instead of inorganic calcium carbonate obtained from limestone, promoting a series of benefits. Thus, the main objective of this research was to determine in which industries this replacement is competent. For this purpose, a review of the literature was carried out where it was possible to determine the characteristics that differentiate both products, as well as a search for the Peruvian industries that import inorganic calcium carbonate. In this way, it was determined that the agriculture/aquaculture, pharmaceutical and food industries meet the characteristics to make the substitution of inorganic calcium carbonate competent for the biogenic one.